Educational scholarship policies for higher education, internationalization, and evaluation of Brazilian graduate programs: A study with panel regression - Mattos, Luísa Karam de; Flach, Leonardo; Mello, Pedro Antônio de (Education Policy Analysis Archives, 2020)
This study aims to analyze the impact of higher education scholarship policies on the internationalization and evaluation of Brazilian postgraduate studies, in the area of Applied Social Sciences, in order to verify if investments by public policies on internationalization of education (e.g., grants) imply an improvement in the concept of quality of Brazilian postgraduate programs. The research method is quantitative, based on panel data regression analysis, correlation between the scholarships abroad granted by the Brazilian public agency Capes, and the evaluation carried out by the institution itself. The period analyzed was from 1998 to 2016, generating a sample of 5,163 observations. Correlation and regression results with panel data show that investment in scholarships abroad has a positive and statistically significant impact on the improvement of postgraduate programs. Furthermore, the results show that investments in scholarships abroad through Capes scholarships are positively correlated with the internationalization of graduate programs in the area of Applied Social Sciences. These results have important implications for policy makers and educational leaders, as they demonstrate the importance of investing in internationalization of higher education to achieve higher levels of excellence.